2016
DOI: 10.1002/job.2154
|View full text |Cite
|
Sign up to set email alerts
|

How negative social interactions at work seep into the home: A prosocial and an antisocial pathway

Abstract: Summary We combined Bakker and Demerouti's spillover–crossover model with Taylor's biobehavioral perspective, tested the comprehensive model, and pursued a set of gender‐related research questions. Negative work interactions were expected to entail two strain responses, high‐ and low‐arousal negative affect. Both should be related to cortisol secretion but transmitted via different social pathways, a positive and a negative one. During a 7‐day ambulatory assessment with 56 couples, we assessed daily variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…In fact, the level of balance between work and family impacts other life domains and is likely to affect not only the individual parent but also those closest to them [ 33 , 37 ], such as the couple and their children [ 35 ]. However, while the impact of the family-work relationship has been extensively studied in couples for example [ 31 , 35 , 37 , 38 , 39 , 40 ], there remain few studies that have assessed the influence of the parental balance between work and family on their children’s well-being [ 5 , 33 , 41 , 42 ]. Strazdins et al [ 43 ] found that unconventional work schedules contributed to depressive symptoms in parents, which negatively affected the well-being of their children.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…In fact, the level of balance between work and family impacts other life domains and is likely to affect not only the individual parent but also those closest to them [ 33 , 37 ], such as the couple and their children [ 35 ]. However, while the impact of the family-work relationship has been extensively studied in couples for example [ 31 , 35 , 37 , 38 , 39 , 40 ], there remain few studies that have assessed the influence of the parental balance between work and family on their children’s well-being [ 5 , 33 , 41 , 42 ]. Strazdins et al [ 43 ] found that unconventional work schedules contributed to depressive symptoms in parents, which negatively affected the well-being of their children.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…Fifty-six couples agreed to participated and provided complete data. The data of three couples could not be analyzed because there was no situation where both partners were together at home after work (for more details, see Klumb et al, 2016). and more than half (58.7%) held a leadership position (leadership span between 1 and 50 collaborators).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The spillover–crossover theory “depicts how job stressors and strains are transmitted from work to the private domain (i.e., spillover) and subsequently to family members via family interactions (i.e., crossover)” (Klumb, Voelkle, & Siegler, , p. 629). Thus, the theory suggests that the family realm is affected by one's work experiences (Bakker, Demerouti, & Dollard, ; Westman, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Emotional contagion therefore occurs to the extent that working mothers' psychological strain affects their family members' level of stress. However, existing research is inconclusive regarding the transmission of job strain from work to home (Klumb et al, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%